Combined modality therapy in Stage IIIA non–small cell lung cancer: clarity or confusion despite the highest level of evidence?. (24th February 2017) - Jeremic, Branislav; Casas, Francesc; Dubinsky, Pavol; Gomez-Caamano, Antonio; Čihorić, Nikola; Videtic, Gregory; Latinovic, Miroslav
Abstract: Recent years have witnessed a number of clinical trials in Stage IIIA non–small cell lung cancer (NSCLC) comparing (A) induction chemotherapy (CHT) with induction CHT and radiotherapy (RT), each followed by surgery; (B) either induction CHT or induction RT-CHT, each followed by surgery, with definitive RT-CHT (no surgery). Due to the heterogeneity of patient, tumor and treatment characteristics across these trials, various meta-analyses (MAs) have been performed to define the optimal treatment approach in this setting for this clinical presentation. Six such MAs exist. In spite of the differences between MAs, it appears that RT does not add extra benefit to induction CHT administered before surgery, and that a trimodality (i.e. including surgery) regimen is not superior to definitive concurrent RT-CHT. While one can consider both induction CHT followed by surgery and exclusive concurrent RT-CHT as feasible in this setting, lack of pre-treatment predictive factors identifying patients who might preferentially benefit from a surgical approach limits its use to well-planned clinical trials.